Rust transforming agent, green rust-free macromolecular anticorrosive paint and method

By developing a green rust-free polymer anti-corrosion coating, using components such as rust converters and film-forming agents, the problems of complex construction, high cost and low efficiency in the existing technology are solved, and the efficient anti-corrosion effect of direct construction on the rusted metal surface is achieved.

CN119529625APending Publication Date: 2025-02-28HUANENG COAL TECH RES CO LTD +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411600394.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is complex when anti-corrosion of metal materials on the surface, the construction is complex, the cost is high, and the efficiency is low. The sandblasting treatment will weaken the strength of the steel structure, and it is difficult to completely remove rust in some dead corners, affecting the anti-corrosion effect of the coating.

Method used

A green rust-free polymer anti-corrosion coating was developed, using a combination of rust converter, film forming agent, curing agent, diluent, defoaming agent and catalyst to synthesize rust converter through polycondensation method and cure it in a low-temperature and humid environment to form a mesh structure with high crosslinking degree to improve the adhesion and impact performance of the coating.

Benefits of technology

This coating can be directly applied to rusted metal surfaces, and can remove rust on the surface. It is simple to construct and has high efficiency, reduces costs, and has significant anti-corrosion effect. Its adhesion and impact performance are better than some rust-free anti-corrosion coatings on the market.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529625A_ABST
    Figure CN119529625A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of anticorrosive coatings for metal equipment, and discloses a rust transforming agent, a green rust-free macromolecular anticorrosive coating and a method. The rust remover comprises the following components in parts by weight: 5-15 parts of a rust conversion agent, 60-80 parts of a film-forming agent, 0.5-5 parts of a curing agent, 10-20 parts of a diluent, 1-5 parts of a defoaming agent and 0.005-0.05 part of a catalyst. According to the product, the site construction requirement is greatly reduced, the working efficiency is improved, and the cost is saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-corrosion coatings for metal equipment, and more specifically, to a rust conversion agent, a green rust-free polymer anti-corrosion coating and a method. Background Art

[0002] The description of the background technology in the present invention belongs to the related technology related to the present invention, which is only used to illustrate and facilitate the understanding of the invention content of the present invention, and should not be understood as the applicant explicitly believes or inferred that the applicant believes that it is the prior art of the present invention on the filing date of the first application.

[0003] Metal materials are corroded by oxygen, moisture and other substances in the atmosphere and rust, which reduces the performance of metal materials, damages mechanical properties and loses performance. According to statistics, metal materials lose about 1% of their total mass every year due to corrosion. At present, paint coating is widely used as the most economical and effective method for surface corrosion protection of metal materials. A protective layer is formed on the metal surface by applying, spraying, electroplating, hot-dip galvanizing or spraying to isolate the corrosive medium from the metal substrate to achieve the purpose of corrosion protection. Generally, before use, the steel substrate needs to be sandblasted to make its surface cleanliness reach Sa2 level or even Sa2.5 level or above to obtain better corrosion resistance.

[0004] The rust removal pretreatment of metal material surface before painting is labor-intensive, inefficient, and expensive, accounting for about 40% of the total project price. Rust dust is very harmful to the human body. Sandblasting will also weaken the strength of steel structure. It is also difficult to completely remove rust in some dead corners. The surface treatment degree of the substrate seriously affects the anti-corrosion effect of the coating. In addition, in some special environments, it is impossible to mechanically or chemically remove rust from the surface of metal equipment in service. It can only be polished manually, with low construction efficiency and poor anti-corrosion effect. Therefore, developing an anti-rust coating that can be directly applied on the rusted surface can greatly simplify the construction process, improve work efficiency, greatly reduce painting costs, and reduce the harm of rust dust to the human body and environmental pollution. Summary of the invention

[0005] In order to reduce the requirements for surface pretreatment of metal materials before painting and solve the problem of difficult construction, the purpose of the embodiments of the present invention is to provide a rust conversion agent, a green rust-free polymer anticorrosive coating and a method, which can be directly applied to rusty metal surfaces. During construction, only the floating rust on the surface needs to be removed, and no surface treatment such as sandblasting is required. It is easy to use and has a good anticorrosive effect, which greatly reduces the requirements for on-site construction, improves work efficiency, and saves costs.

[0006] The purpose of the embodiment of the present invention is achieved through the following technical solutions:

[0007] A green rust-free polymer anticorrosive coating, characterized in that it comprises the following components in parts by weight: 5 to 15 parts of a rust converter, 60 to 80 parts of a film former, 0.5 to 5 parts of a curing agent, 10 to 20 parts of a diluent, 1 to 5 parts of a defoaming agent, and 0.005 to 0.05 parts of a catalyst.

[0008] Furthermore, the rust conversion agent is synthesized by a condensation polymerization method and is synthesized from the following raw materials in parts by weight: 20 to 60 parts of 3-glycidyloxypropylmethyldimethoxysilane, 10 to 40 parts of deionized water, 30 to 70 parts of dimethyldimethoxysilane, 30 to 60 parts of ethanol, 30 to 70 parts of gallic acid, 2 to 10 parts of p-toluenesulfonic acid, and 1 to 10 parts of acetic acid.

[0009] Furthermore, the film-forming agent is epoxy resin.

[0010] Furthermore, the curing agent is a phenolic amine compound.

[0011] Furthermore, the diluent is a compound containing ether bonds and epoxy groups.

[0012] Furthermore, the defoaming agent is an organosilicon defoaming agent.

[0013] Furthermore, the catalyst is a platinum chloride compound.

[0014] A rust conversion agent is synthesized by a polycondensation method and is synthesized from the following raw materials in parts by weight: 20 to 60 parts of 3-glycidyloxypropylmethyldimethoxysilane, 10 to 40 parts of deionized water, 30 to 70 parts of dimethyldimethoxysilane, 30 to 60 parts of ethanol, 30 to 70 parts of gallic acid, 2 to 10 parts of p-toluenesulfonic acid and 1 to 10 parts of acetic acid.

[0015] A method for preparing a rust conversion agent comprises the following steps:

[0016] Gallic acid, ethanol and p-toluenesulfonic acid are added to the reactor in sequence, and after stirring evenly, a mixture of dimethyldimethoxysilane and deionized water is slowly added dropwise. After the addition is completed, the mixture is heated to 50°C to 70°C and reacted for 4h to 6h. Then, a mixture of 3-glycidyloxypropylmethyldimethoxysilane, deionized water and acetic acid is added dropwise, and the reaction is terminated after reacting for 3h to 5h. The final reaction solution is allowed to stand, washed with water, concentrated, and then treated in a vacuum oven to obtain a rust converter.

[0017] A method for preparing a green rust-free polymer anticorrosive coating comprises the following steps:

[0018] Step 1: weigh 5 to 15 parts of rust converter, 60 to 80 parts of film former, 0.5 to 5 parts of curing agent, 10 to 20 parts of diluent, 1 to 5 parts of defoamer, and 0.005 to 0.05 parts of catalyst by weight;

[0019] Step 2: Under electromagnetic stirring, add the rust converter, film-forming agent, diluent and catalyst into the container in sequence, heat and stir in a water bath at 40°C to 50°C for 25min to 40min, until the rust converter is completely dissolved and evenly dispersed, to obtain a mixed material;

[0020] Step 3: Cool the mixture obtained in step 2 to room temperature under stirring;

[0021] Step 4: Add 50% of the diluent, curing agent and defoaming agent to the mixture obtained in step 3 in sequence, and stir at room temperature for 20 to 30 minutes until it is uniform.

[0022] The embodiments of the present invention have the following beneficial effects:

[0023] The present invention provides an environmentally friendly, simple to construct and good anti-corrosion effect rust-free polymer anti-corrosion coating, which is applied to the surface anti-corrosion of in-service metal equipment, thus solving the problems of complex construction, high cost and low efficiency.

[0024] The coating is mainly composed of rust converter, supplemented by film former, curing agent, diluent, defoamer, filler, catalyst, etc. The rust converter contains special polyphenol hydroxyl functional groups, which can fully react with rust, and can generate black complexes or chelates with trivalent iron in rust, so that the surface rust layer can be bonded into a continuous closed coating to seal the entire rust layer and the substrate surface; in addition, the rust converter also contains the same epoxy functional group as the film former epoxy resin, which can be cured in a low temperature and humid environment, and the curing process does not produce harmful volatile substances. After curing, a network structure with a high degree of cross-linking is formed, making the coating denser and improving the adhesion of the coating. At the same time, the rust converter is embedded in the network structure as a flexible segment to improve the impact performance of the coating and make the coating more protective. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A reaction mechanism diagram for preparing intermediate product A;

[0026] Figure 2 A reaction mechanism diagram for preparing intermediate product B;

[0027] Figure 3 A reaction mechanism diagram for preparing a rust conversion agent. DETAILED DESCRIPTION

[0028] The present application is further described below in conjunction with embodiments.

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, in the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. Different embodiments can be replaced or combined, and for ordinary technicians in this field, other implementation methods can be obtained based on these embodiments without creative work.

[0030] A green rust-free polymer anticorrosive coating, characterized in that it comprises the following components in parts by weight: 5 to 15 parts of a rust converter, 60 to 80 parts of a film former, 0.5 to 5 parts of a curing agent, 10 to 20 parts of a diluent, 1 to 5 parts of a defoaming agent, and 0.005 to 0.05 parts of a catalyst.

[0031] In some embodiments of the present invention, the rust conversion agent is synthesized by a condensation polymerization method and is synthesized from the following raw materials in parts by weight: 20 to 60 parts of 3-glycidyloxypropylmethyldimethoxysilane, 10 to 40 parts of deionized water, 30 to 70 parts of dimethyldimethoxysilane, 30 to 60 parts of ethanol, 30 to 70 parts of gallic acid, 2 to 10 parts of p-toluenesulfonic acid, and 1 to 10 parts of acetic acid.

[0032] In some embodiments of the present invention, the film-forming agent is an epoxy resin (E44, E51), which contains epoxy groups and undergoes a chemical reaction to form a cross-linked polymer material.

[0033] In some embodiments of the present invention, the curing agent is a phenolic amine compound, such as curing agent T-31, which can cure epoxy resin under normal temperature and high humidity environment.

[0034] In some embodiments of the present invention, the diluent is a compound containing ether bonds and epoxy groups, such as butyl glycidyl ether. The epoxy groups contained in the molecule participate in the reaction during curing, and no small molecular volatile substances are produced, forming a uniform system. At the same time, the viscosity of the epoxy resin is reduced, making it easy to level.

[0035] In some embodiments of the present invention, the defoaming agent is an organosilicon defoaming agent, the main component of which is organosilane, an oily liquid that is non-volatile at room temperature, inert, physically stable, and has no biological activity.

[0036] In some embodiments of the present invention, the catalyst is a platinum chloride compound.

[0037] A rust conversion agent is synthesized by a polycondensation method and is synthesized from the following raw materials in parts by weight: 20 to 60 parts of 3-glycidyloxypropylmethyldimethoxysilane, 10 to 40 parts of deionized water, 30 to 70 parts of dimethyldimethoxysilane, 30 to 60 parts of ethanol, 30 to 70 parts of gallic acid, 2 to 10 parts of p-toluenesulfonic acid and 1 to 10 parts of acetic acid.

[0038] A method for preparing a rust conversion agent comprises the following steps:

[0039] Gallic acid, ethanol and p-toluenesulfonic acid are added to the reactor in sequence, and after stirring evenly, a mixture of dimethyldimethoxysilane and deionized water is slowly added dropwise. After the addition is completed, the mixture is heated to 50°C to 70°C and reacted for 4h to 6h. Then, a mixture of 3-glycidyloxypropylmethyldimethoxysilane, deionized water and acetic acid is added dropwise, and the reaction is terminated after reacting for 3h to 5h. The final reaction solution is allowed to stand, washed with water, concentrated, and then treated in a vacuum oven to obtain a rust converter.

[0040] A method for preparing a green rust-free polymer anticorrosive coating comprises the following steps:

[0041] Step 1: weigh 5 to 15 parts of rust converter, 60 to 80 parts of film former, 0.5 to 5 parts of curing agent, 10 to 20 parts of diluent, 1 to 5 parts of defoamer, and 0.005 to 0.05 parts of catalyst by weight;

[0042] Step 2: Under electromagnetic stirring, add the rust converter, film-forming agent, diluent and catalyst into the container in sequence, heat and stir in a water bath at 40°C to 50°C for 25min to 40min, until the rust converter is completely dissolved and evenly dispersed, to obtain a mixed material;

[0043] Step 3: Cool the mixture obtained in step 2 to room temperature under stirring;

[0044] Step 4: Add 50% of the diluent, curing agent and defoaming agent to the mixture obtained in step 3 in sequence, and stir at room temperature for 20 to 30 minutes until it is uniform.

[0045] The advantages of the present invention are as follows: the present invention describes a method for synthesizing a highly efficient rust conversion agent, the rust conversion agent having special functional groups: epoxy groups and polyphenolic hydroxyl functional groups. Among them, the polyphenolic hydroxyl can react quickly with rust to form a complex or chelate protective layer, while the epoxy group participates in the cross-linking reaction of the film-forming agent, further improving the compactness and impact resistance of the coating and enhancing the anti-corrosion effect of the coating.

[0046] Example 1

[0047] Taking a specific product manufacturing as an example, the solution of the embodiment of the present invention is further described in detail.

[0048] The rust conversion agent in the green rust-free polymer anticorrosive coating is synthesized by the following specific steps:

[0049] (1) Add 30 parts of gallic acid, 40 parts of ethanol and 2 parts of p-toluenesulfonic acid to a reactor in sequence, stir evenly, and then slowly dropwise add a mixture of 30 parts of dimethyldimethoxysilane and 15 parts of deionized water. After the dropwise addition is completed, heat to 60° C. and react for 5 hours to finally obtain product A;

[0050] (2) 20 parts of 3-glycidyloxypropylmethyldimethoxysilane and 20 parts of ethanol were added to the reactor in sequence, and after stirring evenly, a mixture of 15 parts of deionized water and 3 parts of acetic acid was slowly added dropwise, and the mixture was reacted at room temperature for 1.5 hours to finally obtain product B;

[0051] (3) The product B obtained in (2) is slowly added dropwise to the stirring product A solution, and the temperature is raised to 65° C. to react for 4 hours before the reaction is terminated. The final reaction solution is allowed to stand, washed with water, concentrated, and then treated in a vacuum oven to obtain a rust conversion agent.

[0052] The green rust-free polymer anticorrosive coating is prepared by the following specific steps:

[0053] (1) Weigh 10 parts of rust conversion agent, 70 parts of film-forming agent, 3 parts of curing agent, 15 parts of diluent, 2 parts of defoaming agent, and 0.01 parts of catalyst by weight;

[0054] (2) Under electromagnetic stirring, the rust converter, film-forming agent, diluent and catalyst are added to the container in sequence, and heated and stirred in a water bath at 40° C. for 30 min until the rust converter is completely dissolved and evenly dispersed to obtain a mixed material;

[0055] (3) While stirring, the mixture obtained in step 2 is cooled to room temperature, and then 7.5 parts of diluent, curing agent and defoaming agent are added to the mixture in sequence, and stirred at room temperature for 30 minutes until the mixture is uniform.

[0056] Example 2

[0057] The rust conversion agent in the green rust-free polymer anticorrosive coating is synthesized by the following specific steps:

[0058] (1) Add 45 parts of gallic acid, 40 parts of ethanol and 2 parts of p-toluenesulfonic acid to a reactor in sequence, stir evenly, and then slowly dropwise add a mixture of 50 parts of dimethyldimethoxysilane and 20 parts of deionized water. After the dropwise addition is completed, heat to 60° C. and react for 6 hours to finally obtain product A;

[0059] (2) 40 parts of 3-glycidyloxypropylmethyldimethoxysilane and 20 parts of ethanol were added to the reactor in sequence, and after stirring evenly, a mixture of 20 parts of deionized water and 3 parts of acetic acid was slowly added dropwise, and the mixture was reacted at room temperature for 2 hours to finally obtain product B;

[0060] (3) The product B obtained in (2) is slowly added dropwise to the stirring product A solution, and the temperature is raised to 65° C. to react for 4 hours before the reaction is terminated. The final reaction solution is allowed to stand, washed with water, concentrated, and then treated in a vacuum oven to obtain a rust conversion agent.

[0061] The green rust-free polymer anticorrosive coating is prepared by the following specific steps:

[0062] (1) Weigh 10 parts of rust conversion agent, 70 parts of film-forming agent, 5 parts of curing agent, 13 parts of diluent, 2 parts of defoaming agent, and 0.01 parts of catalyst by weight;

[0063] (2) Under electromagnetic stirring, the rust converter, film-forming agent, diluent and catalyst are added to the container in sequence, and heated and stirred in a water bath at 45° C. for 35 minutes until the rust converter is completely dissolved and evenly dispersed to obtain a mixed material;

[0064] (3) While stirring, the mixture obtained in step 2 is cooled to room temperature, and then 6.5 parts of diluent, curing agent and defoaming agent are added to the mixture in sequence, and stirred at room temperature for 25 minutes until the mixture is uniform.

[0065] Example 3

[0066] The rust conversion agent in the green rust-free polymer anticorrosive coating is synthesized by the following specific steps:

[0067] (1) Add 70 parts of gallic acid, 40 parts of ethanol and 5 parts of p-toluenesulfonic acid to a reactor in sequence, stir evenly, and then slowly dropwise add a mixture of 50 parts of dimethyldimethoxysilane and 30 parts of deionized water. After the dropwise addition is completed, heat to 60° C. and react for 6 hours to finally obtain product A;

[0068] (2) 45 parts of 3-glycidyloxypropylmethyldimethoxysilane and 30 parts of ethanol were added to the reactor in sequence, and after stirring evenly, a mixture of 30 parts of deionized water and 5 parts of acetic acid was slowly added dropwise, and the mixture was reacted at room temperature for 2 hours to finally obtain product B;

[0069] (3) The product B obtained in (2) is slowly added dropwise to the stirring product A solution, and the temperature is raised to 65° C. to react for 4 hours before the reaction is terminated. The final reaction solution is allowed to stand, washed with water, concentrated, and then treated in a vacuum oven to obtain a rust conversion agent.

[0070] The green rust-free polymer anticorrosive coating is prepared by the following specific steps:

[0071] (1) Weigh 10 parts of rust conversion agent, 70 parts of film-forming agent, 8 parts of curing agent, 12 parts of diluent, 2 parts of defoaming agent, and 0.02 parts of catalyst by weight;

[0072] (2) Under electromagnetic stirring, the rust converter, film-forming agent, diluent and catalyst are added to the container in sequence, and heated and stirred in a water bath at 50° C. for 25 min until the rust converter is completely dissolved and evenly dispersed to obtain a mixed material;

[0073] (3) While stirring, cool the mixture obtained in step 2 to room temperature, then add 6 parts of diluent, curing agent and defoaming agent to the mixture in sequence, and stir at room temperature for 20 minutes until the mixture is uniform.

[0074] According to the examples, a rust conversion agent and a green rust-free polymer anticorrosive coating were prepared, and then the green rust-free polymer anticorrosive coating was sprayed on a pre-prepared rusty substrate, wherein the rusty substrate was prepared by an immersion experiment, and the rust layer surface was free of oil stains, water stains, etc. The color change of the coating was observed, and the conversion time and conversion rate were calculated. After the coating was completely dry, its performance was tested, as follows:

[0075] Comparative Example:

[0076] The rust removal pretreatment of the metal material surface before painting is labor intensive, inefficient, and expensive, accounting for about 40% of the total project price. Rust dust is very harmful to the human body. Sandblasting will also weaken the strength of the steel structure. It is also difficult to completely remove rust in individual dead corners. The surface treatment degree of the substrate seriously affects the anti-corrosion effect of the coating. In addition, in some special environments, it is impossible to mechanically or chemically remove rust from the surface of the metal equipment in service. It can only be polished manually, with low construction efficiency and poor anti-corrosion effect. Therefore, developing an anti-rust coating that can be directly applied on the rusted surface can greatly simplify the construction process, improve work efficiency, greatly reduce the cost of painting, and reduce the harm of rust dust to the human body and environmental pollution. After the coating is actually dry, the adhesion performance is greatly improved compared with some rust-free anti-corrosion coatings (4.1MPa) currently on the market, and it does not distinguish between primer and topcoat, and only needs to be applied once, which greatly shortens the construction time.

[0077]

[0078] It should be noted that the above embodiments can be freely combined as needed. The above description is only the preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A green rust-free polymer anticorrosive coating, characterized in that: The invention comprises the following components in parts by weight: 5 to 15 parts of rust conversion agent, 60 to 80 parts of film former, 0.5 to 5 parts of curing agent, 10 to 20 parts of diluent, 1 to 5 parts of defoaming agent and 0.005 to 0.05 parts of catalyst.

2. A green rust-free polymer anticorrosive coating according to claim 1, characterized in that: The rust conversion agent is synthesized by a polycondensation method and is synthesized from the following raw materials in parts by weight: 20 to 60 parts of 3-glycidyloxypropylmethyldimethoxysilane, 10 to 40 parts of deionized water, 30 to 70 parts of dimethyldimethoxysilane, 30 to 60 parts of ethanol, 30 to 70 parts of gallic acid, 2 to 10 parts of p-toluenesulfonic acid and 1 to 10 parts of acetic acid.

3. The green rust-free polymer anticorrosive coating according to claim 1, characterized in that: The film-forming agent is epoxy resin.

4. The green rust-free polymer anticorrosive coating according to claim 1, characterized in that: The curing agent is a phenolic amine compound.

5. The green rust-free polymer anticorrosive coating according to claim 1, characterized in that: The diluent is a compound containing ether bonds and epoxy groups.

6. The green rust-free polymer anticorrosive coating according to claim 1, characterized in that: The defoamer is an organosilicon defoamer.

7. The green rust-free polymer anticorrosive coating according to claim 1, characterized in that: The catalyst is a platinum chlorate compound.

8. A rust conversion agent, characterized in that The rust conversion agent is synthesized by a polycondensation method and is synthesized from the following raw materials in parts by weight: 20 to 60 parts of 3-glycidyloxypropylmethyldimethoxysilane, 10 to 40 parts of deionized water, 30 to 70 parts of dimethyldimethoxysilane, 30 to 60 parts of ethanol, 30 to 70 parts of gallic acid, 2 to 10 parts of p-toluenesulfonic acid and 1 to 10 parts of acetic acid.

9. A method for preparing a rust conversion agent, characterized in that: The steps include: Gallic acid, ethanol and p-toluenesulfonic acid are added to the reactor in sequence, and after stirring evenly, a mixture of dimethyldimethoxysilane and deionized water is slowly added dropwise. After the addition is completed, the mixture is heated to 50°C to 70°C and reacted for 4h to 6h. Then, a mixture of 3-glycidyloxypropylmethyldimethoxysilane, deionized water and acetic acid is added dropwise, and the reaction is terminated after reacting for 3h to 5h. The final reaction solution is allowed to stand, washed with water, concentrated, and then treated in a vacuum oven to obtain a rust converter.

10. A method for preparing a green rust-free polymer anticorrosive coating, characterized in that: The steps include: Step 1: weigh 5 to 15 parts of rust converter, 60 to 80 parts of film former, 0.5 to 5 parts of curing agent, 10 to 20 parts of diluent, 1 to 5 parts of defoamer, and 0.005 to 0.05 parts of catalyst by weight; Step 2: Under electromagnetic stirring, add the rust converter, film-forming agent, diluent and catalyst into the container in sequence, heat and stir in a water bath at 40°C to 50°C for 25min to 40min, until the rust converter is completely dissolved and evenly dispersed, to obtain a mixed material; Step 3: Cool the mixture obtained in step 2 to room temperature under stirring; Step 4: Add 50% of the diluent, curing agent and defoaming agent to the mixture obtained in step 3 in sequence, and stir at room temperature for 20 to 30 minutes until it is uniform.

Citation Information

Patent Citations

  • Preparation method and application of sol dispersion liquid

    CN108586812A

  • Water-based organosilicon sol coating, preparation method thereof and product

    CN109810631A

  • High-solid-content rust-removal-free anticorrosive paint for metal and preparation method of rust-removal-free anticorrosive paint

    CN113174188A

  • Solvent-free rust conversion amorphous anticorrosive paint and preparation method thereof

    CN118652604A

  • Excellent corrosion-proof performance organic-inorganic hybridized coatings and its prepn. method

    CN1831070A